Evaluasi Kelayakan Geometrik Tikungan Pada Ruas Jalan Jenderal Ahmad Yani Km. 2 Kota Parepare - Nurul; Sulfanita, Andi; Fadly, Imam (Jurnal Karajata Engineering, 2024)
Jendral Ahmad Yani Km. 2 road is one of the land transportation accesses that connects between regions in improving the economy and standard of living of the community. This study aims to analyze the geometrics of road bends. The research method used is descriptive quantitative method of analysis using the standards of the Directorate of Highways. The results of the research from the geometric bend results that the road section includes a primary collector function class SCS type bend with provincial road status with type 2/2 UD. The existing geometric conditions of the road section are in accordance with the required standards where there is a vertical alignment of 8.1% and a stopping sight distance of 133.36m. Coordination of alignments that coincide does not obstruct visibility.